Correction to: prevalence of and risk factors for malaria, filariasis, and intestinal parasites as single infections or co-infections in different settlements of Gabon, Central Africa - Noé Patrick M'bondoukwé; Eric Kendjo; Denise Patricia Mawili-Mboumba; Jeanne Vanessa Koumba Lengongo; Christelle Offouga Mbouoronde; Dieudonné Nkoghe; Fousseyni Touré; Marielle Karine Bouyou-Akotet (BMC, 2018)
Unfortunately, the original article [1] contained some errors. The table title of Tables 4, 5, 6, 7 were interchanged by mistake and displayed incorrectly in the article. The correct table titles of Tables 4, 5, 6, 7 can be found below.